Surveillance of intradomiciliary contacts of leprosy cases: perspective of the client in a hyperendemic municipality - Helizandra Simoneti Bianchini Romanholo; Eliana Amorim de Souza; Alberto Novaes Ramos Júnior; Adélia Cileode Gomes Castelo Branco Kaiser; Ismália Oliveira da Silva; Aline Lima Brito; Cídia Vasconcellos
ABSTRACT Objective: To characterize approach methods for intradomiciliary contacts (IdC) of leprosy cases resident in Northern Brazil, during 2001-2012. Method: A cross-sectional and descriptive study in the state of Rondônia. Included IdC of leprosy cases diagnosed/reported in SINAN-Ministry of Health (MS), 2001-2012. A semi-structured instrument was applied to the IdCs, with six interventions: complete dermatological examination; complete neurological examination; BCG vaccination; instructions for return to the health unit; BCG guidance; and guidance to mobilize other contacts. Results: From a total of 459 IdCs included, failure to perform the dermatological examination was reported by 191 people (41.6%) and the neurological examination, by 252 (54.9%); 138 (30.1%) did not have BCG indicated and 122 (26.6%) did not receive guidelines; 257 (56.0%) were not advised to return for a new evaluation/follow-up and 186 (40.5%) were not asked to mobilize other contacts. Conclusion: Despite the favorable indicators of IdC examination coverage in the state, the evaluation process presents patterns that indicate operational quality failures.